Marital conflict, negative temperament and problem behaviors of children: A test of stability and variability across time - Sween, Molly (2011)
Drawing on transactional family systems as the guiding theoretical perspective, this research uses the dataset, National Survey of Family and Households to assess the ways that marital conflict and negative attributes of children (i.e. negative temperament and problem behaviors) may mutually influence one another over three Waves of data. According to this perspective, the family, similar to other systems or social institutions within society, consists of interrelated subsystems that impact and shape one another across time. As such, I predicted that marital conflict and negative attributes of children mutually influence one another over time which was tested through running cross-lagged structural equation models. Results show that within-wave effects (i.e. reciprocal) are present between marital conflict and negative child temperament in childhood (Wave 1) as well as between marital conflict and problem behaviors in adolescence (Wave 2). This indicates that marital conflict and negative child attributes demonstrate a stronger relationship contemporaneously rather than across time (i.e. no cross-lagged effects were found)